2010
DOI: 10.1126/science.1195701
|View full text |Cite
|
Sign up to set email alerts
|

Thought for Food: Imagined Consumption Reduces Actual Consumption

Abstract: The consumption of a food typically leads to a decrease in its subsequent intake through habituation--a decrease in one's responsiveness to the food and motivation to obtain it. We demonstrated that habituation to a food item can occur even when its consumption is merely imagined. Five experiments showed that people who repeatedly imagined eating a food (such as cheese) many times subsequently consumed less of the imagined food than did people who repeatedly imagined eating that food fewer times, imagined eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
230
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(265 citation statements)
references
References 29 publications
22
230
6
Order By: Relevance
“…Cross-sectional and intervention studies have documented that adherence to a guided imagery program is correlated with greater motivation to be physically active [47,54,55]. Similarly, a growing body of literature suggests that guided imagery can be effective at improving dietary behaviors [48,56,57]. These studies suggest that guided imagery may be an effective way to simultaneously increase smoking cessation and engagement with physical activity and dietary behaviors.…”
Section: Introductionmentioning
confidence: 96%
“…Cross-sectional and intervention studies have documented that adherence to a guided imagery program is correlated with greater motivation to be physically active [47,54,55]. Similarly, a growing body of literature suggests that guided imagery can be effective at improving dietary behaviors [48,56,57]. These studies suggest that guided imagery may be an effective way to simultaneously increase smoking cessation and engagement with physical activity and dietary behaviors.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, research in the domain of sensory habituation has suggested that people will prefer the first sensoryrich product in a sequence (i.e., primacy effects) because there is likely to be decreased sensitivity to, or liking of, repeated exposure to a stimulus (Epstein et al 2009;Morewedge, Huh, and Vosgerau 2010). Sensory habituation has been explained from both physiological and neurological perspectives.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Following this logic, participants in Exp. 2 completed a reinforcement game modeled after classic studies of animal motivation (36)(37)(38)(39)(40). In a typical experiment of this type, the number of times that a rat pressed a lever indexed the rat's motivation to obtain a food reward associated with that lever (such that hungry rats would demonstrate greater effort and persistence in lever-pressing than nonhungry rats).…”
Section: Preliminary Experimentsmentioning
confidence: 99%